Influența aprecierii calității vieții asupra stărilor emoționale la pacienții cu artrită reumatoidă [Articol] - Condrea, Victoria (CEP USM, 2020)
The research presents the study of defence mechanisms and quality of life in patients with rheumatoid arthritis and ostheoarthritis. The research aims to identify the relationship between defence mechanisms and quality of life in these patients. The present research is determined by the rapid evolution and development of humanity in order to increase material comfort but simultaneously ignoring the spiritual one.
Keywords: psihologie medicală; calitatea vieții; stări emoționale